Ceramic Electronic Components

JP7629494B2Active Publication Date: 2025-02-13TAIYO YUDEN KK
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023146229
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-09-08
Publication Date
2025-02-13
Estimated Expiration
2040-10-30

AI Technical Summary

Benefits of technology

【0014】 本発明によれば、寿命特性を向上させることができるセラミック電子部品を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007629494000002
    Figure 0007629494000002
  • Figure 0007629494000003
    Figure 0007629494000003
  • Figure 0007629494000004
    Figure 0007629494000004
Patent Text Reader

Abstract

To provide a ceramic electronic component whose lifetime characteristic can be improved.SOLUTION: A ceramic electronic component includes a multilayer chip in which a plurality of dielectric layers mainly containing ceramics and a plurality of internal electrode layers are stacked. The internal electrode layers contain Ni, Sn, and Au. In a thickness direction of the dielectric layer, there is a concentration gradient in which the concentration of Au and the concentration of Sn gradually decrease from the interface part with the internal electrode layer to the inside.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a ceramic electronic component. [Background technology]

[0002] Ni (nickel) is used for the internal electrodes of ceramic electronic components such as multilayer ceramic capacitors. In the firing process, a reducing atmosphere is often used to prevent oxidation of Ni. However, if the firing process is performed in a reducing atmosphere, oxygen defects may be generated in the dielectric layer, which may deteriorate the reliability. Therefore, a technology has been disclosed that improves the reliability of the capacitor by incorporating Sn into the Ni internal electrodes (see, for example, Patent Documents 1 and 2). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] WO 14 / 024538 [Patent Document 2] Special Publication No. 2005-505695 Summary of the Invention [Problem to be solved by the invention]

[0004] However, when Ni is used in the internal electrodes, there is room for improvement in the life characteristics of ceramic electronic components.

[0005] The present invention has been made in consideration of the above-mentioned problems, and has an object to provide a ceramic electronic component that can improve the life characteristics. [Means for solving the problem]

[0006] The ceramic electronic component according to the present invention comprises a laminated chip in which a plurality of dielectric layers mainly composed of ceramic and a plurality of internal electrode layers are laminated, and the internal electrode layers contain Ni, Sn, and Au.

[0007] In the internal electrode layers of the ceramic electronic component, the total content of Sn and Au relative to Ni may be 0.01 at % or more and 95 at % or less.

[0008] In the internal electrode layers of the ceramic electronic component, the total content of Sn and Au relative to Ni may be 0.2 at % or more and 10 at % or less.

[0009] In the internal electrode layers of the ceramic electronic component, the Au content may be less than the Sn content.

[0010] In the ceramic electronic component, the internal electrode layer may have a higher Sn concentration in the vicinity of the interface with the dielectric layer than in a central portion in the thickness direction.

[0011] In the internal electrode layers of the ceramic electronic component, a concentration of Au may be higher in the vicinity of the interface with the dielectric layer than in a central portion in a stacking direction.

[0012] A method for producing a ceramic electronic component according to the present invention is characterized by comprising the steps of: forming an internal electrode pattern containing Ni, Sn, and Au on a dielectric green sheet to form a laminate unit; laminating a plurality of the laminate units to form a laminate; and firing the laminate.

[0013] In the above-described method for manufacturing a ceramic electronic component, the step of forming the laminated unit may be a step of forming the internal electrode pattern on the dielectric green sheet by a vacuum film formation process. Effect of the Invention

[0014] According to the present invention, it is possible to provide a ceramic electronic component that can improve the life characteristics. [Brief description of the drawings]

[0015] [Figure 1] FIG. 2 is a partial cross-sectional perspective view of a multilayer ceramic capacitor. [Diagram 2] 2 is a cross-sectional view taken along line AA in FIG. 1. [Diagram 3] FIG. 2 is a cross-sectional view taken along line BB in FIG. [Figure 4] FIG. 13 is a diagram showing the effect of an added element in an internal electrode layer on the diffusion of Ni. [Diagram 5] FIG. 4A is a diagram illustrating an example of the Sn concentration in the internal electrode layers, and FIG. 4B is a diagram illustrating an example of the Au concentration in the internal electrode layers. [Figure 6] 1A to 1C are diagrams illustrating a flow of a method for manufacturing a multilayer ceramic capacitor. [Figure 7] 1(a) and (b) are diagrams illustrating the lamination process. [Figure 8] FIG. 11 is a Weibull plot diagram showing the relationship between the time until failure and the cumulative failure rate for the examples and the comparative examples. [Figure 9] 6(a) to 6(c) are diagrams showing the Ni concentration in the dielectric layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] Hereinafter, an embodiment will be described with reference to the drawings.

[0017] (Embodiment) FIG. 1 is a partial cross-sectional perspective view of a multilayer ceramic capacitor 100 according to an embodiment. FIG. 2 is a cross-sectional view taken along line AA in FIG. 1. FIG. 3 is a cross-sectional view taken along line BB in FIG. 1. As illustrated in FIGS. 1 to 3, the multilayer ceramic capacitor 100 includes a laminated chip 10 having a substantially rectangular parallelepiped shape, and external electrodes 20a, 20b provided on two opposing end faces of the laminated chip 10. Of the four faces of the laminated chip 10 other than the two end faces, the two faces other than the upper and lower faces in the lamination direction are referred to as side faces. The external electrodes 20a, 20b extend on the upper, lower and two side faces in the lamination direction of the laminated chip 10. However, the external electrodes 20a, 20b are spaced apart from each other. In FIG. 1, the X-axis direction (first direction) is the length direction of the laminated chip 10, the direction in which the two end faces of the laminated chip 10 face each other, and the direction in which the external electrodes 20a and 20b face each other. The Y-axis direction (second direction) is the width direction of the internal electrode layers. The Z-axis direction is the stacking direction. The X-axis direction, the Y-axis direction, and the Z-axis direction are perpendicular to each other.

[0018] The laminated chip 10 has a configuration in which dielectric layers 11 containing a ceramic material that functions as a dielectric and internal electrode layers 12 containing a base metal material are alternately laminated. The edges of the internal electrode layers 12 are alternately exposed to the end face on which the external electrode 20a of the laminated chip 10 is provided and the end face on which the external electrode 20b is provided. As a result, each internal electrode layer 12 is alternately conductive to the external electrode 20a and the external electrode 20b. As a result, the laminated ceramic capacitor 100 has a configuration in which a plurality of dielectric layers 11 are laminated via the internal electrode layers 12. In addition, in the laminate of the dielectric layers 11 and the internal electrode layers 12, the internal electrode layers 12 are arranged on the outermost layer in the lamination direction, and the upper and lower surfaces of the laminate are covered by the cover layer 13. The cover layer 13 is mainly composed of a ceramic material. For example, the material of the cover layer 13 is the same as that of the dielectric layers 11 and the ceramic material.

[0019] The size of the multilayer ceramic capacitor 100 is, for example, 0.25 mm in length, 0.125 mm in width, and 0.125 mm in height, or 0.4 mm in length, 0.2 mm in width, and 0.2 mm in height, or 0.6 mm in length, 0.3 mm in width, and 0.3 mm in height, or 1.0 mm in length, 0.5 mm in width, and 0.5 mm in height, or 3.2 mm in length, 1.6 mm in width, and 1.6 mm in height, or 4.5 mm in length, 3.2 mm in width, and 2.5 mm in height, but is not limited to these sizes.

[0020] The dielectric layer 11 is mainly composed of a ceramic material having a perovskite structure represented by the general formula ABO3. 3-α For example, the ceramic material includes BaTiO3 (barium titanate), CaZrO3 (calcium zirconate), CaTiO3 (calcium titanate), SrTiO3 (strontium titanate), BaTiO3 (strontium titanate) which forms a perovskite structure, 1-x-y Ca x Sr y Ti 1-z Zr z O3 (0≦x≦1, 0≦y≦1, 0≦z≦1), etc. can be used. The thickness of each dielectric layer 11 is, for example, 0.05 μm or more and 5 μm or less, or 0.1 μm or more and 3 μm or less, or 0.2 μm or more and 1 μm or less.

[0021] 2, a region where the internal electrode layer 12 connected to the external electrode 20a and the internal electrode layer 12 connected to the external electrode 20b face each other is a region that generates capacitance in the multilayer ceramic capacitor 100. Therefore, the region that generates capacitance is referred to as a capacitance region 14. In other words, the capacitance region 14 is a region where adjacent internal electrode layers 12 connected to different external electrodes face each other.

[0022] The region where the internal electrode layers 12 connected to the external electrode 20a face each other without an internal electrode layer 12 connected to the external electrode 20b being interposed therebetween is referred to as the end margin 15. The region where the internal electrode layers 12 connected to the external electrode 20b face each other without an internal electrode layer 12 connected to the external electrode 20a being interposed therebetween is also the end margin 15. In other words, the end margin 15 is a region where the internal electrode layers 12 connected to the same external electrode face each other without an internal electrode layer 12 connected to a different external electrode being interposed therebetween. The end margin 15 is a region that does not generate capacitance.

[0023] 3, in the laminated chip 10, the regions extending from the two side surfaces of the laminated chip 10 to the internal electrode layers 12 are referred to as side margins 16. That is, the side margins 16 are regions provided to cover the ends of the multiple internal electrode layers 12 stacked in the above-mentioned laminated structure that extend to the two side surfaces. The side margins 16 are also regions that do not generate electrical capacitance.

[0024] In such a multilayer ceramic capacitor 100, if Ni is used for the internal electrode layer 12, there is a risk that oxygen defects will occur in the dielectric layer 11, and the reliability of the dielectric layer 11 will deteriorate. For example, if a reducing atmosphere is used in the firing process to suppress oxidation of Ni, oxygen defects are likely to occur in the dielectric layer 11. If the dielectric layer 11 in which oxygen defects have occurred is thinned and a voltage of high electric field strength is applied, the durability of the dielectric layer 11 will be insufficient. In this case, there is a risk that the life characteristics of the multilayer ceramic capacitor 100 will deteriorate, such as the life being shortened or varying. Therefore, the multilayer ceramic capacitor 100 according to this embodiment has a configuration that improves the life characteristics.

[0025] First, the internal electrode layer 12 contains Sn in addition to Ni. When the internal electrode layer 12 contains Ni and Sn, the life of the multilayer ceramic capacitor 100 can be improved. For example, it is believed that the life of the multilayer ceramic capacitor 100 is improved by changing the state of the interface between the internal electrode layer 12 and the dielectric layer 11 due to the alloying of Ni and Sn.

[0026] Next, although the mechanism is not clear, it has been recognized that when Ni contained in the internal electrode layer 12 diffuses into the dielectric layer 11, the multilayer ceramic capacitor 100 tends to have a short life. Therefore, it is required to suppress the diffusion of Ni from the internal electrode layer 12 to the dielectric layer 11. Therefore, the present inventors investigated the effect of an additive element to the internal electrode layer 12 on the diffusion of Ni.

[0027] First, four types of samples were prepared. As the first sample, a sample was prepared in which an internal electrode pattern made of Ni (thickness 200 nm) was formed by sputtering on a dielectric green sheet mainly composed of barium titanate. As the second sample, a sample was prepared in which 3.3 μg of Ni paste was printed on a dielectric green sheet mainly composed of barium titanate. As the third sample, a sample was prepared in which an internal electrode pattern containing Ni and Sn (Sn 3.2 atm%, thickness 200 nm) was formed by sputtering on a dielectric green sheet mainly composed of barium titanate. As the fourth sample, a sample was prepared in which an internal electrode pattern containing Ni and Au (Au 1.0 atm%, thickness 200 nm) was formed by sputtering on a dielectric green sheet mainly composed of barium titanate.

[0028] For each sample, oxygen partial pressure of 10 -5 atm~10 -8 The samples were prepared by firing at 1100°C to 1300°C in a reducing atmosphere of 1 atm. The Ni concentration in the dielectric layer was measured using La-ICP (laser ablation fusion ion plasma mass spectrometry). The relationship between the distance from the internal electrode layer and the Ni concentration ratio (Ni / Ti) atm% was measured.

[0029] FIG. 4 shows the results. As shown in FIG. 4, for the first to third samples, the Ni concentration was high even in areas away from the internal electrode layers. This is believed to be because Ni diffused during firing. In contrast, for the fourth sample, the Ni concentration was low in areas away from the internal electrode layers. This is believed to be because Ni diffusion was suppressed during firing. From these results, it was confirmed that the addition of Au to the internal electrode layers suppresses Ni diffusion into the dielectric layers.

[0030] Therefore, the internal electrode layer 12 according to this embodiment contains Sn in addition to Ni, and also contains Au. When the internal electrode layer 12 further contains Au, Au has a function of barrier against diffusion of Ni, and diffusion of Ni into the dielectric layer 11 is further suppressed. This improves the durability of the dielectric layer 11 against application of a voltage of high electric field strength. As a result, the life of the multilayer ceramic capacitor 100 is improved. By improving the life, short life is not included, and variation in life is also suppressed. Therefore, the life characteristics of the multilayer ceramic capacitor 100 are improved.

[0031] The thickness of the internal electrode layer 12 is, for example, 0.01 μm or more and 5 μm or less, or 0.05 μm or more and 3 μm or less, or 0.1 μm or more and 1 μm or less.

[0032] If the Sn content in the internal electrode layer 12 is low, the state of the interface between the internal electrode layer 12 and the dielectric layer 11 may not be sufficiently controlled. If the Au content is low, the diffusion of Ni may not be sufficiently suppressed. Therefore, it is preferable to set a lower limit for the total of the Sn content and the Au content. For example, in the internal electrode layer 12, the total of the Sn content and the Au content relative to Ni is preferably 0.01 at% or more, more preferably 0.05 at% or more, even more preferably 0.1 at% or more, and even more preferably 0.2 at% or more.

[0033] On the other hand, if the total of the Sn content and the Au content is high, problems such as a decrease in melting point and an increase in cost may occur. Therefore, it is preferable to set an upper limit on the total of the Sn content and the Au content. For example, in the internal electrode layer 12, the total of the Sn content and the Au content relative to Ni is preferably 95 at% or less, more preferably 50 at% or less, and even more preferably 10 at% or less.

[0034] In addition, if the sum of the Sn content and the Au content is 0.2 at% or more and 10 at% or less, even if the Au content is less than the Sn content, it is possible to suppress the diffusion of Ni while controlling the state of the interface between the internal electrode layer 12 and the dielectric layer 11. Therefore, if the sum of the Sn content and the Au content is 0.2 at% or more and 10 at% or less, it is preferable that the Au content is less than the Sn content from the viewpoint of reducing the amount of Au used and lowering costs.

[0035] In addition, it is preferable that the Sn concentration is high in the vicinity of the interface between the dielectric layer 11 and the internal electrode layer 12 in the internal electrode layer 12. This is because the reliability is not determined by the entire internal electrode layer, but only by the vicinity of the interface between the dielectric layer 11 and the internal electrode layer 12. Therefore, as illustrated in FIG. 5(a), it is preferable that the internal electrode layer 12 has a concentration gradient such that the Sn concentration is low in the center in the thickness direction and high in the vicinity of the interface with the dielectric layer 11. Also, as illustrated in FIG. 5(b), it is preferable that the Au concentration is high in the vicinity of the interface with the dielectric layer 11 in the internal electrode layer 12. This is because the diffusion of Ni into the dielectric layer 11 can be efficiently suppressed. Therefore, it is preferable that the internal electrode layer 12 has a concentration gradient such that the Au concentration is low in the center in the stacking direction and high in the vicinity of the interface with the dielectric layer 11.

[0036] Next, a description will be given of a method for manufacturing the multilayer ceramic capacitor 100. FIG 6 is a diagram illustrating a flow of the method for manufacturing the multilayer ceramic capacitor 100.

[0037] (Raw powder production process) First, a dielectric material for forming the dielectric layer 11 is prepared. The A-site elements and B-site elements contained in the dielectric layer 11 are usually contained in the dielectric layer 11 in the form of a sintered body of ABO3 particles. For example, BaTiO3 is a tetragonal compound having a perovskite structure and exhibits a high dielectric constant. This BaTiO3 can generally be obtained by synthesizing barium titanate by reacting a titanium raw material such as titanium dioxide with a barium raw material such as barium carbonate. Various methods have been known so far as a method for synthesizing the main component ceramic of the dielectric layer 11, such as a solid-phase method, a sol-gel method, a hydrothermal method, and the like. In this embodiment, any of these methods can be adopted.

[0038] A predetermined additive compound is added to the obtained ceramic powder according to the purpose. The additive compound may be an oxide of magnesium (Mg), manganese (Mn), vanadium (V), chromium (Cr), rare earth elements (yttrium (Y), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm) and ytterbium (Yb)), or an oxide containing cobalt (Co), nickel, lithium (Li), boron (B), sodium (Na), potassium (K) or silicon (Si), or a glass containing cobalt, nickel, lithium, boron, sodium, potassium or silicon.

[0039] For example, a compound containing an additive compound is wet-mixed with a ceramic raw material powder, and then dried and pulverized to prepare a ceramic material. For example, the ceramic material obtained as described above may be pulverized as necessary to adjust the particle size, or may be combined with a classification process to adjust the particle size. Through the above steps, a dielectric material is obtained.

[0040] (Lamination process) Next, a binder such as polyvinyl butyral (PVB) resin, an organic solvent such as ethanol or toluene, and a plasticizer are added to the obtained dielectric material and wet mixed. The obtained slurry is used to coat a dielectric green sheet 52 having a thickness of, for example, 0.5 μm to 1.0 μm on a substrate 51 by, for example, a die coater method or a doctor blade method, and then dried. The substrate 51 is, for example, a PET (polyethylene terephthalate) film.

[0041] Next, as illustrated in Fig. 7(a), an internal electrode pattern 53 is formed on a dielectric green sheet 52. In Fig. 7(a), as an example, four layers of internal electrode patterns 53 are formed on the dielectric green sheet 52 at a predetermined interval. The film formation method is not particularly limited, but may be, for example, using an electrode paste containing a mixture of Ni-Sn-Au, mixing a component containing Au or Sn into a paste of Ni metal powder, vacuum film formation such as sputtering using an alloy target, or simultaneous sputtering using individual targets. The dielectric green sheet 52 on which the internal electrode pattern 53 is formed is defined as a lamination unit.

[0042] Next, while peeling off the dielectric green sheet 52 from the base material 51, the lamination units are laminated as shown in FIG. 7(b).

[0043] Next, a predetermined number of cover sheets (e.g., 2 to 10 layers) are laminated on the top and bottom of the laminate obtained by laminating the lamination units, and are thermocompression bonded, and then cut into a predetermined chip size (e.g., 1.0 mm x 0.5 mm). In the example of Fig. 7(b), cutting is performed along the dotted lines. The cover sheet may have the same components as the dielectric green sheet 52, or may have a different additive compound.

[0044] (Firing process) The ceramic laminate thus obtained was subjected to binder removal treatment in a N2 atmosphere, after which a metal paste that would become the undercoat layers of the external electrodes 20a and 20b was applied thereto by a dipping method, and the ceramic laminate was then subjected to a dipping treatment in a nitrogen atmosphere under an oxygen partial pressure of 10 -5 ~10 -8The laminated ceramic capacitor 100 is thus obtained, and is then fired in a reducing atmosphere of 1 atm at 1100 to 1300° C. for 10 minutes to 2 hours.

[0045] (Reoxidation treatment process) After that, a re-oxidation treatment may be performed at 600°C to 1000°C in an N2 gas atmosphere.

[0046] (Plating process) Thereafter, the external electrodes 20a, 20b may be coated with a metal such as Cu, Ni, Sn, etc. by plating.

[0047] According to the manufacturing method of this embodiment, the internal electrode layer 12 contains Sn in addition to Ni, and also contains Au. This improves the life of the obtained multilayer ceramic capacitor 100. The improved life eliminates short lifespans, and suppresses variation in lifespan. This improves the life characteristics of the multilayer ceramic capacitor 100.

[0048] In the above embodiments, a multilayer ceramic capacitor has been described as an example of a ceramic electronic component, but the present invention is not limited to this. For example, other electronic components such as a varistor or a thermistor may be used. EXAMPLES

[0049] The multilayer ceramic capacitor according to the embodiment was fabricated and its characteristics were examined.

[0050] Example 1 Additives were added to the barium titanate powder, and the mixture was thoroughly wet mixed and pulverized in a ball mill to obtain a dielectric material. A butyral-based organic binder, toluene and ethyl alcohol were added to the dielectric material as a solvent, and a dielectric green sheet was applied onto a PET substrate by the doctor blade method. The thickness of the dielectric green sheet was 1.0 μm.

[0051] Next, an internal electrode pattern was formed on the dielectric green sheet using a paste containing a Ni-Sn-Au alloy. The Ni / Sn / Au ratio was 96 / 2 / 2 in atomic ratio.

[0052] Next, the laminate units were laminated while peeling off the dielectric green sheet from the substrate. The temperature during lamination was 80°C. After lamination of the laminate units, a pressure of 4 MPa was applied and pressed. The pressing time was 5 seconds. Next, a predetermined number of cover sheets were laminated on the top and bottom of the laminate obtained by laminating the laminate units, and thermocompression bonded by hydrostatic pressure. The hydrostatic pressure was 120 MPa, the temperature was 100°C, and the pressing time was 25 seconds. Then, it was cut to the predetermined chip dimensions (1.0 mm x 0.5 mm x 0.5 mm).

[0053] The ceramic laminate thus obtained was subjected to a binder removal treatment in an N2 atmosphere, after which a metal paste that would become the underlayer of the external electrodes was applied thereto by a dipping method, and then fired in a reducing atmosphere.

[0054] Example 2 A multilayer ceramic capacitor was produced under the same production conditions as in Example 1, except that the atomic ratio of Ni / Sn / Au was changed to 99.6 / 0.2 / 0.2.

[0055] Example 3 A multilayer ceramic capacitor was produced under the same production conditions as in Example 1, except that the atomic ratio of Ni / Sn / Au was changed to 80 / 10 / 10.

[0056] Comparative Example 1 Neither Sn nor Au was added to the internal electrode layers. The other manufacturing conditions were the same as in Example 1.

[0057] Comparative Example 2 The internal electrode layers were doped with Au at the same concentration as in Example 1, but no Sn was added. The other manufacturing conditions were the same as in Example 1.

[0058] Comparative Example 3 The internal electrode layers were doped with Sn at the same concentration as in Example 1, but no Au was added. The other manufacturing conditions were the same as in Example 1.

[0059] (Life test) The time to failure was measured for a plurality of samples for each of Examples 1 to 3 and Comparative Examples 1 to 3. The measurement method was to measure the time until the leakage current became 10 times the minimum leakage current under a DC electric field of 150° C. / 18 V / μm.

[0060] Fig. 8 is a Weibull plot diagram showing the relationship between the time to failure and the cumulative failure rate for each of Examples 1 to 3 and Comparative Examples 1 to 3. Table 1 shows the slope of the Weibull plot in Fig. 8. Table 1 also shows the time at which 50% of the samples failed for each of Examples 1 to 3 and Comparative Examples 1 to 3. [Table 1]

[0061] As shown in FIG. 8 and Table 1, in Comparative Example 1, the slope of the Weibull plot was gentle, and many samples had short life spans. In addition, the difference in life span between samples was large. This is believed to be because the internal electrode layer did not contain Sn or Au. In Comparative Example 2, the life span was longer than that of Comparative Example 1, but a sufficient life span was not obtained. This is believed to be because only Sn was added to the Ni of the internal electrode layer without adding Au, so the diffusion of Ni was not sufficiently suppressed. In Comparative Example 3, the life span was longer than that of Comparative Example 1, but a sufficient life span was not obtained. This is believed to be because only Au was added to the Ni of the internal electrode layer without adding Sn, so the interface between the internal electrode layer and the dielectric layer was not sufficiently controlled.

[0062] In contrast, in Examples 1 to 3, the lifespan was sufficiently long for all samples. In addition, the slope of the Weibull plot was large, and the variation in lifespan was also suppressed. This is believed to be because the internal electrode layer contained both Sn and Au in addition to Ni.

[0063] The Ni concentration in the dielectric layer was measured using La-ICP for Example 1 and Comparative Examples 2 and 3. FIG. 9(a) is a diagram showing the results of Comparative Example 3. FIG. 9(b) is a diagram showing the results of Comparative Example 2. FIG. 9(c) is a diagram showing the results of Example 1. As shown in FIG. 9(a), when Au was not added to the internal electrode layer, a lot of Ni was diffused in the dielectric layer. In contrast, as shown in FIG. 9(b), when Au was added to the internal electrode layer instead of Sn, it was found that the amount of Ni diffused into the dielectric layer was suppressed. Furthermore, as shown in FIG. 9(c), when both Sn and Au were added to the internal electrode layer, it was found that the amount of Ni diffused into the dielectric layer was further suppressed. In this way, it was found that the diffusion of Ni into the dielectric layer was further suppressed by the internal electrode layer containing both Sn and Au. It is considered that these results are the factors that led to the results in Table 1.

[0064] Although the embodiments of the present invention have been described in detail above, the present invention is not limited to such specific embodiments, and various modifications and variations are possible within the scope of the gist of the present invention described in the claims. [Explanation of symbols]

[0065] 10 Stacked Chip 11 Dielectric layer 12 Internal electrode layer 13 Cover Layer 14 capacity area 15 End Margin 16 Side Margin 20a,20b external electrode 51 Base material 52 Dielectric green sheet 53 Internal electrode pattern 100 Multilayer ceramic capacitors

Claims

1. The laminated chip includes a plurality of dielectric layers mainly made of ceramic and a plurality of internal electrode layers laminated together, The internal electrode layers include Ni, Sn, and Au, In the internal electrode layers, the total content of Sn and Au relative to Ni is 0.01 at% or more and 95 at% or less; A ceramic electronic component, characterized in that a concentration gradient is formed in the thickness direction of the dielectric layer such that the Au concentration and the Sn concentration gradually decrease from the interface with the internal electrode layer toward the inside.

2. 2. The ceramic electronic component according to claim 1, wherein in the internal electrode layers, a total content of Sn and Au relative to Ni is 0.2 at % or more and 10 at % or less.

3. 3. The ceramic electronic component according to claim 1, wherein the Au content is less than the Sn content in the internal electrode layers.

4. 4. The ceramic electronic component according to claim 1, wherein the internal electrode layer has a higher Sn concentration in the vicinity of the interface with the dielectric layer than in a central portion in the thickness direction.

5. 4. The ceramic electronic component according to claim 1, wherein the internal electrode layers have a higher concentration of Au in the vicinity of the interface with the dielectric layer than in a central portion in a stacking direction.

6. 6. The ceramic electronic component according to claim 1, wherein in the internal electrode layers, a total of a Sn content and a Au content relative to Ni is 0.2 at % or more and 10 at % or less, and the Au content is less than the Sn content.

7. A laminated chip including a plurality of dielectric layers mainly made of ceramic and a plurality of internal electrode layers laminated together, The internal electrode layers include Ni, Sn, and Au, In the internal electrode layers, the Au content is less than the Sn content, A ceramic electronic component, characterized in that a concentration gradient is formed in the thickness direction of the dielectric layer such that the Au concentration and the Sn concentration gradually decrease from the interface with the internal electrode layer toward the inside.

Citation Information

Patent Citations

  • Capacitor electrode composition

    JP1985133717A

  • Precious metal-containing resinate paste for preparing internal electrode for ceramic multi-layer capacitor

    JP1996169788A

  • Powder for use inside multilayer ceramic capacitor electrodes

    JP2005505695A

  • Electronic component

    JP2010153485A

  • Multilayer ceramic capacitor

    JP2018198292A